Forecasting a moving target: The roles of quality and timing for determining northern U.S. Wheat basis - Bekkerman, A.; Brester, G. W.; Taylor, Mykel R. (My University, 2016)
While nearly instantaneous commodity futures price information provides price forecasts for national markets, many market participants are interested in forecasts of local cash prices. Expected basis estimates are often used to convert futures prices into local price forecasts. This study considers basis patterns in the northern U.S. hard red spring and hard red winter wheat markets. Using data on basis values across 215 grain-handling facilities, we empirically test the forecasting capabilities of numerous basis models. Contrary to basis models developed for other U.S. regions, we show that recent futures prices, protein content, and harvest information are more important for accurate basis forecasts than historical basis averages. The preferred basis models are used to develop an automated web-based basis forecasting tool, available at http://wheatbasis.Montana.edu. Copyright 2016 Western Agricultural Economics Association.
Citation: Bekkerman, A., Brester, G. W., & Taylor, M. (2016). Forecasting a moving target: The roles of quality and timing for determining northern U.S. Wheat basis. Journal of Agricultural and Resource Economics, 41(1), 25-41. Retrieved from https://www.scopus.com/inward/record.uri?eid=2-s2.0-84955444036&partnerID=40&md5=5269e2afe2c206ad381f66e84019281d
Keywords: Basis; Forecast; Protein; Spring Wheat; Winter Wheat